Intension of health checkup for cardiovascular disease prevention and its determinants among people of age 30-59 years living in Madhyapur Thimi municipality, Bhaktapur, Nepal. - Poudel, Manju (2020)
ABSTRACT: Introduction: Cardiovascular diseases (CVD) are the leading cause of disease burden and deaths globally. Of these deaths, 85% are due to heart attack and stroke. STEPS Survey 2019 in Nepal revealed that percentage of people of age 15-69 with at least one risk factor of non communicable disease is around 78.8 percent. The objective of this study was to assess intention of health check up for cardiovascular disease prevention and its determining factors among people of age 30-59 years living in Madhyapur Thimi Municipality, Bhaktapur, Nepal. Method: A cross-sectional descriptive study was conducted in Madhyapur Thimi Municipality, Bhaktapur with 600 respondents of age 30-59 years. Two stage cluster sampling technique was applied for selecting household. Face to face interview technique was used. Coding and entry was done in EpiData 3.1 version and data was analyzed in SPSS version 16. Descriptive, bivariate and multivariate analysis was done. Results: Regarding degree of likeliness for health checkup within 1 year, less than half of the respondents (40.7%) have positive intention to go for health checkup for CVD prevention. Nearly two third respondents (59.3%) do not have any intention. Age above 42 years (AOR: 1.866,95% CI: 1.190 - 2.927), educational status (AOR: 2.387, 95% CI: 1.170- 4.870), diabetic (AOR: 4.113, 95% CI: 1.901-8.896), hypertensive (AOR: 2.970, 95% CI:1.626-5.423), high blood cholesterol level (AOR: 2.278, 95% CI: 1.032-5.028), awareness about stroke (AOR: 1.823, 95% CI:1.175- 2.827), perceived self at risk of CVD (AOR: 2.665, 95% CI: 1.652-4.302) and perceived no drawbacks of CVD health checkup (AOR: 2.151, 95% CI: 1.444-3.203) are the determining factors of intension of health checkup for CVD prevention. Conclusion: Prevalence of positive intention for health checkup for CVD prevention is low in this study. Priority should be given to public health program focusing on the importance and benefit of early CVD health checkup at community level.